A discrete two-level model for charge pricing of electric vehicles based on evolution game theory. Issue 1 (1st February 2017) - Liang, Dong; Li, Hui; Yang, Guoqing; Yang, N.N.; Zhang, Huizhi; Jia, Rong
Abstract : According to the present vehicle-to-grid situation and existing pricing strategy in China, this paper proposed a two-level evolution game model for pricing analysis problem. The model contains two level game models: the up level game operated between monopoly electricity sale enterprise and small electricity sale enterprise; the second level is game between electricity sale enterprise and EV user; a pay-off matrix in ternary nonlinear equation form is built to descries the evolution process under different strategies. After the Linearization of nonlinear equations, the evolution stable strategy (ESS) is deduced for evolution game model. Analysis work is carried out depending on the ESS. Finally, the numerical results are given by computer simulation. Several suggestions of pricing strategies in China's electricity market are obtained.